Amount of Water Sufficient to Suppress Thermal Decomposition of Forest Fuel; Journal of Mechanics; Vol. 33 - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Zhdanova A. O. Alena Olegovna (2017, 2017)
Title screen